m6A Reader YTHDC2 Promotes Radiotherapy Resistance of Nasopharyngeal Carcinoma via Activating IGF1R/AKT/S6 Signaling Axis - He, Jun-Ju; Li, Zhi; Rong, Zhuo-Xian; Gao, Jie; Mu, Yun; Guan, Yi-Di; Ren, Xin-Xin; Zi, Yu-Yuan; Liu, Li-Yu; Fan, Qi; Zhou, Ming; Duan, Yu-Mei; et al. (Frontiers in Oncology, 2020)
N6-methyladenosine (m6A) modification has been reported as a critical regulator of gene transcript expression. Although m6A modification plays important roles in tumor development, its role in therapeutic resistance remains unknown. In this study, we aimed to examine the expression level of m6A-modification related proteins and elucidate the effect of m6A-related proteins on radiation response in nasopharyngeal carcinoma (NPC). Among the genes that participated in m6A modification, YTHDC2, a m6A reader, was found to be consistently highly expressed in radioresistant NPC cells. Knocking down of YTHDC2 expression in radioresistant NPC cells improved the therapeutic effect of radiotherapy in vitro and in vivo, whereas overexpression of YTHDC2 in radiosensitive NPC cells exerted an opposite effect. Bioinformatics and mechanistic studies revealed that YTHDC2 could physically bound to insulin-like growth factor 1 receptor (IGF1R) messenger RNA and promoted translation initiation of IGF1R mRNA, which in turn activated the IGF1R-AKT/S6 signaling pathway. Thus, the present study suggests that YTHDC2 promotes radiotherapy resistance of NPC cells by activating the IGF1R/ATK/S6 signaling axis and may serve as a potential therapeutic target in radiosensitization of NPC cells.